2021
DOI: 10.3390/molecules26206291
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics and Physiological Insights into the Ability of Exogenously Applied Chlorogenic Acid and Hesperidin to Modulate Salt Stress in Lettuce Distinctively

Abstract: Recent studies in the agronomic field indicate that the exogenous application of polyphenols can provide tolerance against various stresses in plants. However, the molecular processes underlying stress mitigation remain unclear, and little is known about the impact of exogenously applied phenolics, especially in combination with salinity. In this work, the impacts of exogenously applied chlorogenic acid (CA), hesperidin (HES), and their combination (HES + CA) have been investigated in lettuce (Lactuca sativa L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…However, the extracts seemed to be more than just a plant regulator due to the presence of molecules such as phenolic compounds. The addition of exogenous phenolics has been previously reported to enhance plant performance [75]. In particular, Zhang et al [75] showed that the addition of chlorogenic acid and hesperidin alleviates the impact of salt stress by improving photosynthetic performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the extracts seemed to be more than just a plant regulator due to the presence of molecules such as phenolic compounds. The addition of exogenous phenolics has been previously reported to enhance plant performance [75]. In particular, Zhang et al [75] showed that the addition of chlorogenic acid and hesperidin alleviates the impact of salt stress by improving photosynthetic performance.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of exogenous phenolics has been previously reported to enhance plant performance [75]. In particular, Zhang et al [75] showed that the addition of chlorogenic acid and hesperidin alleviates the impact of salt stress by improving photosynthetic performance. Moreover, Zhang et al [76] pointed out that the addition of phenolics, including hesperidin, can modulate functional traits in lettuces, also modifying the endogenous phenolic content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenolic profiles of different D. maritima extracts were analyzed using a UHPLC-QTOF-MS (Agilent Technologies, Stevens Creek Blvd, Santa Clara, CA, USA). The instrument parameters and methods adopted for the analysis were optimized in previous works [ 66 , 67 ]. Regarding chromatographic separation, it was achieved by using an Agilent InfinityLab Poroshell 120 pentafluorophenyl (PFP) column (2.1 × 100 mm, 1.9 μm) (Agilent Technologies, Stevens Creek Blvd, Santa Clara, CA, USA) and a binary mixture of water and acetonitrile acidified with 0.1% ( v / v ) formic acid as mobile phase (LC-MS grade, VWR, Milan, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…The raw metabolomic data set was transformed and normalized in Mass Profiler Professional B.15.1 (Agilent Technologies, Stevens Creek Blvd, Santa Clara, CA, USA). Therefore, chemometric interpretation such as Principal component analysis (PCA) was performed by using MetaboAnalyst 5.0 ( accessed on 10 December 2022), while the orthogonal projection to latent structures discriminant analysis (OPLS-DA) was created using SIMCA 16 software (Umetrics, Malmo, Sweden), as previously described [ 67 ]. To validate and to investigate outliers of the OPLS-DA model, the model fitness parameters (goodness of fit: R 2 Y; goodness of prediction: Q 2 Y; cross-validation: CV-ANOVA, p < 0.01) were determined, and permutation test ( n = 100) and Hotelling’s T2 (95% and 99% confidence limit for the suspect and strong outliers, respectively) performed [ 71 ].…”
Section: Methodsmentioning
confidence: 99%